PELATIHAN PEMBUATAN GAME EDUKASI KAHOOT BAGI GURU DI SMA NEGERI 1 PAJANGAN, BANTUL - Kintoko kintoko; Dani Kusuma; Ferani Mulianingsih; Andri Suryaningsih (LPPM Universitas Abdurrab, 2024)
The purpose of this community service project is to provide guidance to the teachers of SMAN 1 Pajangan in creating educational Kahoot games. Subject matter experts at the school participated in the program, which took place in August. Various types of educational games, their advantages and disadvantages, as well as recent research on the benefits of using educational games for learning, were covered in the introduction to this activity. Additionally, the main objective of this community service is to offer fresh insights to the teachers of SMAN 1 Pajangan on the advantages of Kahoot educational games, the features of the website, and how to create them. The method used in this community service involved three stages: the pre-activity stage, the activity implementation stage, and the post-activity stage. The outcome of this training is to make teachers more creative in developing teaching modules that will be delivered to students, thereby enhancing student learning outcomes, accelerating material comprehension, making learning more engaging and less monotonous, and increasing learning interest. The conclusion of this community service is that it equips teachers to utilize Kahoot as a learning medium. It is recommended for educators to develop their teaching processes by incorporating Kahoot as a medium.